(untitled) (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
This community service aims to provide an explanation about socialization of role for parents in children for the development of children’s character and explain about digital readings to parents of students "School Committee" Madrasah Ibtidaiyah, Mount Bunder II, RW 4, Pamijahan, Bogor, West Java. The development of character education can be said to be a moral education, ethics, value, and character education whose goal is to develop a child’s ability to make good decisions, bad, nurturing goodness, manifesting and spreading Good in everyday life. Community service activities that form socialization counseling about the role of parents in strengthening the development of children in the character of this child is very important because in today’s digital era. The development and culture of today’s digital era among adolescents increasingly demonstrates that the occurrence of the social crisis of the character is quite attentive. The development of the character of social attitudes is not only the work of teachers in schools, but it is a joint task in the family, both teachers, parents, religious figures, society and other stakeholders. For that in educating the child in this digital era, parents in the family should be aware that technological advances cannot be abandoned. Therefore, parents ’ foster patterns should be selected for a democratic but controlled foster pattern. This foster pattern is not authoritarian but democratic in encouraging children to communicate development and educate children in family education.